Migration and Politics in South Africa: Mainstreaming Anti-immigrant Populist Practice - Machinya, Johannes (African Human Mobility Review, 2022)
In 1994, a ‘new’ South Africa was born out of electoral democracy. While democratisation dismantled minority authoritarian rule as well as legalised racial intolerance, prejudicial and discriminatory practices remained, this time directed against foreigners. This is at variance with South Africa’s commitment to principles of liberal democracy, human rights, and regional integration. What then explains this paradox? This paper underscores that what feeds and bestows social legitimacy to xenophobia is the foregrounding of an anti-immigrant populist discourse in the mainstream political discourse with participation of political leaders from across the political spectrum. But how has a morally repugnant anti-immigrant populist practice been made a sensible and justifiable political narrative? The paper analyses the mediated populist performances of selected political leaders like press statements, public speeches, interviews, or other statements posted on social media platforms like Twitter, and how these leaders scapegoat foreigners for the challenges the country is facing.